Academic outcomes of inclusive education in typically developing children - Bakoč, Andrijana; Brojčin, Branislav; Banković, Slobodan; Glumbić, Nenad; Đorđević, Mirjana (Frontiers in Psychology, 2025)
IntroductionThe fact that inclusive education has existed in Bosnia and Herzegovina for twenty years opens the question of how it affects typically developing children, among other things. This paper aims to examine the differences in general knowledge and mathematics of typically developing students with regard to whether they attend classes that include students with intellectual disabilities or not, as well as to determine the relationship of their knowledge with teachers’ characteristics and the inclusiveness of schools they attend.MethodsThe sample included 331 students from 18 regular elementary school classes. The sample was divided into two subsamples – respondents who attended classes that included students with intellectual disabilities and respondents who attended classes that did not include any students with disabilities. The Peabody Individual Achievement Test – revised was used to assess general knowledge and mathematics, while My Thinking About Inclusion Scale, Bender Classroom Structure Questionnaire, Teacher Efficacy for Inclusive Practices, and Inclusive Process Evaluation Scale were used for assessing the teacher and school variables.ResultsNo statistically significant difference was found between the two subsamples. The schools’ inclusiveness was related to better achievements of all respondents, mainly in terms of work organization. The examined teachers’ characteristics established different relationships with academic achievements in different subsamples.ConclusionAttending classes with a student with intellectual disability did not negatively affect the academic achievements of other students in class. The school’s inclusiveness in terms of work organization was positively related to the academic achievement of all students, while the relation of teachers’ characteristics with students’ achievements is a complex phenomenon that requires further research. Given the results obtained, to achieve better academic outcomes, teachers in classrooms attended by students with intellectual disability should be encouraged to use metacognitive and individualized teaching strategies. Furthermore, school principals and school administration would contribute to the success of all students by organizing the school on the principles of inclusion.